2022
DOI: 10.1097/md.0000000000030150
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endometrial scratching on reproductive outcome in patients: A systematic review and meta-analysis

Abstract: Background: Endometrial scratching (ES) has demonstrated initial success in women with recurrent implantation failure, but the effect in women with 1 previous assisted reproductive technology (ART) failure is unknown. This meta-analysis aimed to evaluate the impact of ES as a treatment in clinical outcomes for women with at least 1 failed in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI)/Intrauterine Insemination (IUI).Methods: PubMed, Medline, Embase, Cochrane Library, Web of Science, CNKI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Findings from this study suggest that patients who underwent endometrial scratch using the Shepard catheter have significantly lower pain scores compared to those who underwent the Pipelle. Low to moderate pain and discomfort are commonly reported by patients who received the Pipelle for endometrial biopsy (7,8,10). However, to our knowledge, no prior studies have assessed pain scores and ART outcomes using the Shepard catheter compared to the standard Pipelle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from this study suggest that patients who underwent endometrial scratch using the Shepard catheter have significantly lower pain scores compared to those who underwent the Pipelle. Low to moderate pain and discomfort are commonly reported by patients who received the Pipelle for endometrial biopsy (7,8,10). However, to our knowledge, no prior studies have assessed pain scores and ART outcomes using the Shepard catheter compared to the standard Pipelle.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial scratch, a procedure that involves intentional disruption of the endometrium prior to embryo transfer, may increase endometrial receptivity and implantation (4)(5)(6). However, while some studies suggest that endometrial scratch prior to embryo transfer may improve implantation rates and clinical pregnancy rates, patients report experiencing moderate pain and discomfort during the endometrial scratch procedure (6)(7)(8)(9)(10) Endometrial scratch is associated with significantly higher pain scores compared to patients who did not receive endometrial scratch during ART (11). In a multicenter randomized control trial of 1,364 patients, the median pain score reported by patients who underwent endometrial scratch was 3.5 out of 10 on a visual analogue scale (IQR=1.9-6.0) (Lensen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For a more detailed insight, many reviews and meta-analytic publications were published concerning this topic, which seems to be declining but is still under a heated debate (reviewed i.a. in [ 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 ]).…”
Section: Clinical Significance In Reproductive Medicinementioning
confidence: 99%
“…Recurrent implantation failure Thin endometrial lining Scratching [171][172][173][174][175][176][177][178], PRP infusion [183][184][185][186][187][188], G-CSF [267,269,270] Wound-healing-like Decidualization, Regeneration…”
Section: Balanced Inflammatory Micromilieumentioning
confidence: 99%
“…Nevertheless, ES was not recommended for women undergoing their first IVF cycle but was supposed to be a tool for patients with multiple implantation failures [8,10,11]. From the initial reports on ES, the infertility community controversially assessed these results, and a common point of criticism was the fact that the physiology and subsequent changes of the endometrium executed by the procedure were and are still unclear [12,13]. However, ES is not only applied for the purpose of possibly enhancing pregnancy rates but also as a procedure to gain endometrial tissue for diagnostic investigations such as the detection of uterine natural killer cells (uNK), plasma cells (PC), and Endometrial Receptivity Analysis (ERA) [14].…”
Section: Introductionmentioning
confidence: 99%